Supplementary Example 6
Last updated at April 16, 2024 by Teachoo
Supplementary examples and questions from CBSE
Supplementary Example 2 Important Deleted for CBSE Board 2025 Exams
Supplementary Example 3 Deleted for CBSE Board 2025 Exams
Supplementary Example 4 Deleted for CBSE Board 2025 Exams
Supplementary Example 5 Important Deleted for CBSE Board 2025 Exams
Supplementary Example 6 Deleted for CBSE Board 2025 Exams You are here
Supplementary Exercise Q1 Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q2 Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q3 Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q4 Important Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q5 Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q6 Important Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q7 Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q8 Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q9 Important Deleted for CBSE Board 2025 Exams
Supplementary Exercise Q10 Deleted for CBSE Board 2025 Exams
Supplementary examples and questions from CBSE
Last updated at April 16, 2024 by Teachoo
Supplementary Example 6 For any three vectors ∴ 𝑎 ⃗, 𝑏 ⃗, and 𝑐 ⃗, prove that [■8(𝑎 ⃗" + " 𝑏 ⃗&𝑏 ⃗+𝑐 ⃗&𝑐 ⃗+𝑎 ⃗ )] = 2 [𝑎 ⃗ , 𝑏 ⃗, 𝑐 ⃗] To prove [■8(𝑎 ⃗" + " 𝑏 ⃗&𝑏 ⃗+𝑐 ⃗&𝑐 ⃗+𝑎 ⃗ )] = 2 [𝑎 ⃗ , 𝑏 ⃗, 𝑐 ⃗] Solving LHS [■8(𝑎 ⃗" + " 𝑏 ⃗&𝑏 ⃗+𝑐 ⃗&𝑐 ⃗+𝑎 ⃗ )] = (𝑎 ⃗" + " 𝑏 ⃗). ["(" 𝑏 ⃗+𝑐 ⃗") " × " (" 𝑐 ⃗+𝑎 ⃗)] = (𝑎 ⃗" + " 𝑏 ⃗). ["(" 𝑏 ⃗×𝑐 ⃗") + (" 𝑏 ⃗×𝑎 ⃗)+"(" 𝒄 ⃗×𝒄 ⃗") + (" 𝑐 ⃗×𝑎 ⃗)] = "(" 𝑎 ⃗+𝑏 ⃗")." [(𝑏 ⃗×𝑐 ⃗") + (" 𝑏 ⃗×𝑎 ⃗ ) "+ 0 + (" 𝑐 ⃗" × " 𝑎 ⃗") " ] = 𝑎 ⃗. (𝑏 ⃗ × 𝑐 ⃗) + 𝑏 ⃗.(𝑏 ⃗ × 𝑐 ⃗) + 𝑎 ⃗. (𝑏 ⃗ × 𝑎 ⃗) + 𝑏 ⃗.(𝑏 ⃗ × 𝑎 ⃗) + 𝑎 ⃗.(𝑐 ⃗ × 𝑎 ⃗) + 𝑏 ⃗.(𝑐 ⃗ × 𝑎 ⃗) = [𝑎 ⃗", " 𝑏 ⃗", " 𝑐 ⃗ ] + [𝒃 ⃗", " 𝒃 ⃗", " 𝒄 ⃗ ] + [𝒂 ⃗", " 𝒃 ⃗", " 𝒂 ⃗ ] + [𝒃 ⃗", " 𝒃 ⃗", " 𝒂 ⃗ ] + [𝒂 ⃗", " 𝒄 ⃗", " 𝒂 ⃗ ] + [𝑏 ⃗", " 𝑐 ⃗", " 𝑎 ⃗ ] [𝑏 ⃗", " 𝑏 ⃗", " 𝑐 ⃗ ] = [𝑐 ⃗", " 𝑏 ⃗", " 𝑏 ⃗ ] = 𝑐 ⃗. (𝑏 ⃗ × 𝑏 ⃗) As (𝑏 ⃗ × 𝑏 ⃗) = 0 ⃗ = 𝑐 ⃗ . 0 ⃗ = 0 ⃗ Using Prop: [𝑏 ⃗", " 𝑏 ⃗", " 𝑐 ⃗ ] = 0 [𝑎 ⃗", " 𝑏 ⃗", " 𝑎 ⃗ ] = 0 [𝑏 ⃗", " 𝑏 ⃗", " 𝑎 ⃗ ] = 0 [𝑎 ⃗", " 𝑐 ⃗", " 𝑎 ⃗ ] = 0 = [𝑎 ⃗", " 𝑏 ⃗", " 𝑐 ⃗ ] + 0 + 0 + 0 + 0 + [𝑏 ⃗", " 𝑐 ⃗", " 𝑎 ⃗ ] = [𝑎 ⃗", " 𝑏 ⃗", " 𝑐 ⃗ ] + [𝒃 ⃗", " 𝒄 ⃗", " 𝒂 ⃗ ] = [𝑎 ⃗", " 𝑏 ⃗", " 𝑐 ⃗ ] + [𝒂 ⃗", " 𝒃 ⃗", " 𝒄 ⃗ ]